Mouse vs wild - Stilton, Geronimo; Dami, Elisabetta (Geronimo Stilton, 2022)
"When you're with Geronimo Stilton, it's always a fabumouse adventure! Trap had finally talked me into taking a relaxing vacation. But it turned out it wouldn't just be given to me. We were going to have to win it! I was on my way to Port Stinky to win a race against the wild. Could I stand the smell long enough to win?"--